Penyelesaian Tindak Pidana Ringan Melalui Komunikasi Mediasi Lembaga Adat - Musrizal; Syamsul Bahri; Maisarah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
This research is important to explain about minor criminal acts, which are acts committed by someone who violates the public interest which is threatened with sanctions or fines. The legal basis for the settlement of minor crimes that can be carried out by the Adat Qanun Institution Number 9 of 2008 concerning the Development of Customary Life, Article 13 Paragraph (1) regulates that there are 18 cases or disputes that are delegated resolutions through the Adat Court in Aceh, as well as Court Regulations. Agung (Perma) Number 2 of 2012 regulates the limit on the value of minor crimes. The settlement of minor crimes committed by the Gampong Customary Institution always makes it easier for the parties in the settlement process. The settlement carried out by the Customary Institution is to hold deliberations and summon the parties to facilitate the settlement process for the minor criminal case. The settlement of the crime is carried out at the meunasah in a fast and easy way and does not require money. Meanwhile, the sanctions given by the Gampong Customary Institution are also in accordance with the capabilities and habits prevailing in the local community. The role of the Customary Institution in every dispute resolution, where Adat always strives to maintain a balance between the reporter and the reported and the sanctions that are wise and fair for both parties, so that the parties get a sense of justice and no one feels disadvantaged.